SAFETY AND EFFICACY OF PERCUTANEOUS RENAL BIOPSY AS SAME DAY OUTPATIENT PROCEDURE - Syed Sajid Hussain Shah; Naureen Akhtar; Faiza Sunbleen (Journal of University Medical & Dental College, 2015)
ABSTRACT: BACKGROUND: Renal biopsy is the gold standard in nephrology, not only for diagnosis of renal diseases but also deﬁning the management, prognosis and outcome. OBJECTIVE: To assess the safety and efﬁcacy of the renal biopsy as an outpatient basis procedure with same day admission and discharge. DESIGN: Observational study. MATERIALS AND METHODS: This study had been conducted at Nephrology Department, The Children’s Hospital and The Institute of Child Health, Lahore form 15 January 2014 till 14 January 2015. Total of 169 paedaitric patients having kidney disease who underwent renal biopsy were included as their their admission day, discharge day, biopsy day and complications were taken in account as before procedure patients were screened for bleeding diathesis. After renal biopsy patients were monitored for any complication and patients who showed no complication and stable were discharged from hospital on same day of biopsy. RESULTS: Total of 169 patients included, 109(64.5%) were male and 60(35.5%) were females. The age range was from 0.7 to 16 years. 59(34.9%) patients were admitted on same day and renal biopsy was done while 110(65.1%) patients were admitted before the procedure day for renal biopsy. Ninety patients were admitted one day prior for renal biopsy and renal biopsy was done next day. About 88.7% patients were discharged on same day after the procedures. Hematuria was observed in 4.7% patients. CONCLUSION: Renal biopsy is a safe procedure which can be easily done and successfully accomplished as an outpatient procedure with minimum complications as this reduces ﬁnancial and logistic burden.